Epidemiological characteristics of the carriers with coexistence of HBsAg and anti‐HBs based on a community cohort study. Issue 4 (14th December 2015) - Pu, Z.; Li, D.; Wang, A.; Su, H.; Shao, Z.; Zhang, J.; Ji, Z.; Gao, J.; Choi, B. C. K.; Yan, Y.
Summary: The coexistence of HBsAg and anti‐HBs is an atypical serological pattern in HBV infection. There is no epidemiological characteristics of this serological pattern in the community and there is controversy over the molecular mechanisms underlying this pattern. We investigated the epidemiological characteristics of the carriers with HBsAg and anti‐HBs in a longitudinal community cohort study. The prevalence of this atypical serological pattern was 2.93% (122/4169) in HBsAg‐positive populations. The prevalence progressively increased with age from 40 to 70 years old. The rate of HBeAg positive and detectable HBV DNA were both significantly higher in carriers with this pattern than in carriers who were HBsAg positive but anti‐HBs negative (26/122 verse 598/4047, P = 0.046; 86/122 verse 275/529, P < 0.001). After 1 year of follow‐up, 85.19% of the carriers still had coexistence HBsAg and anti‐HBs, 14.81% of the carriers lost their anti‐HBs. Viral sequencing showed that carriers with coexistence of HBsAg and anti‐HBs had higher numbers of residue changes within the S gene than carriers who were HBsAg positive but anti‐HBs negative (2.42 verse 1.33 changes per 100 residues, P < 0.05). Hence, the coexistence of HBsAg and anti‐HBs is a unique serological pattern which may be associated with an increased risk of adverse clinical outcome and may be related to HBsAg immune variants which have genotypic heterogeneity.